2002
DOI: 10.1046/j.1525-1594.2002.06877.x
|View full text |Cite
|
Sign up to set email alerts
|

Online Hemodiafiltration Versus Acetate‐Free Biofiltration: A Prospective Crossover Study

Abstract: Online hemodiafiltration (online HDF) and acetate-free biofiltration (AFB) are 2 innovative renal replacement therapies. Convincing evidence has shown that both techniques are superior to conventional hemodialysis in many aspects. The aim of the present investigation was to compare online HDF and AFB in 12 stable maintenance hemodialysis patients in a prospective, randomized crossover trial. Twelve stable dialysis patients, age 49.7 +/- 11.3 years and on dialysis for 83.5 +/- 76.7 months, were treated prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In low flux dialysis protein removal only occurs with adsorptive membranes (PMMA, polyacrilonitrile) with decreasing dialysis efficacy for water soluble toxins (Parzer et al, 1993). This removal of albumin can be compensated after a time of about 12 weeks in the absence of relevant inflammation (Ding et al, 2002;Kaysen et al, 1997). In chronic ambulant peritoneal dialysis protein losses are in-between 6 to 10 g/d and albumin losses up to 5 g/d over the peritoneal membrane (Kaysen et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In low flux dialysis protein removal only occurs with adsorptive membranes (PMMA, polyacrilonitrile) with decreasing dialysis efficacy for water soluble toxins (Parzer et al, 1993). This removal of albumin can be compensated after a time of about 12 weeks in the absence of relevant inflammation (Ding et al, 2002;Kaysen et al, 1997). In chronic ambulant peritoneal dialysis protein losses are in-between 6 to 10 g/d and albumin losses up to 5 g/d over the peritoneal membrane (Kaysen et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that in olHDF the ESA dosage needed to reach the hemoglobin goal is reduced (Vaslaki et al, 2006;Bonforte et al, 2002;Eiselt et al, 2000). The efficacy of dialysis measured by single pool Kt/V could be improved (Ahrenholz et al, 1997;Ding et al, 2002). There is evidence of longer survival of patients treated by olHDF versus hemodialysis (HD) independently of dialysis dosage (Canaud et al, 2008;Panicchi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective long-term cross-over study comparing on-line 180 ml/min pre-dilution and 60-80 ml/min post-dilution hemodiafiltration to acetate-free biofiltration with infusion of 20-30 ml/min isotonic bicarbonate solution, the differences in biochemistry parameters among the three modalities of treatment were not remarkable and the reduction rate of ß 2 -microglobulin is not statistically different [29]. These data open the debate of the optimal volume of ultrafiltration and substitution fluid.…”
Section: Alternatives To Hemodiafiltrationmentioning
confidence: 97%
“…Although most dialysates now contain 3-5 mEq/L of acetate, this has been suggested to have a clinical effect when infused as part of a large volume replacement fluid [59]. Implementation of acetate-free HDF potentially reduces the risk of intra-dialytic hypotension [60] after the long inter-dialytic interval, although this technique typically leads to a greater positive sodium balance, and has not been shown to provide greater cardiovascular stability compared to high-volume online HDF [61]. …”
Section: Incremental Regimes and Alternative Approaches To Preserve Rrfmentioning
confidence: 99%